Have you seen my dragon? - Light, Steve (Somerville, Massachusetts : Candlewick Press, 2014)
Invite young readers to practice counting to twenty while helping a small boy search the city for his pet dragon.
Keywords: Dragons -- Fiction; Lost and found possessions -- Fiction; Counting -- Fiction; Dragons -- Fiction; Lost and found possessions -- Fiction; Counting -- Fiction